Association between Socioeconomic and Demographic Factors with Electronic Waste Generation in Jakarta - Adzania, F. H.; Zakianis; Wulandari, R. A.; Ambarsari, R.; Fauzia, S.; Aryati, G. P. (Annali di Igiene Medicina Preventiva e di Comunità, 2023)
Background. Electronic waste is a continuously increasing hazardous and toxic waste in this digital era. Socioeconomic and demographic status contribute to the increase in electronic waste generation. Study design. Ecological study. Methods. The aim of this study was to analyze the socioeconomic and demographic factors that are related to the increase of e-waste generation in 44 sub-districts in Jakarta. Data from the Jakarta Provincial Environment Department, Statistics Indonesia, and Open Data Jakarta were used for this study. Data were analyzed using correlation tests. Results. The results show that the increase in electronic waste generation is related to the male gender (p = 0.036, r = 0.316) and a moderate education level (p = 0.038, r =0.313). Conclusions. We recommend that the Jakarta Provincial Government provides electronic waste collection points in all areas; however, the area in which its population is dominated by males and has a moderate education level should be prioritized.